Acute Suppurative Parotitis in a 22-Day-Neonate with Sepsis: A Rare Case Report - Mine Özdil; Derya Erçin (Cam & Sakura Medical Journal, 2024)
Acute neonatal suppurative parotitis is a very rare condition that causes parotid swelling and purulent exudation into the oral cavity through the Stenson duct. The prognosis is usually excellent, but may be complicated by sepsis, meningitis, and abscesses. A case of sepsis and unilateral suppurative parotitis in a 22-day-old male infant successfully treated with intravenous antibiotics is presented here. Although rare, acute suppurative parotitis can be discovered in neonates, especially in 2-4 weeks of age, and is mostly caused by Staphylococcus aureus. Prompt diagnosis, appropriate intravenous antibiotics, and adequate hydration should be initiated immediately to prevent complications.